Commodity Price Movements and Banking Crises. - Eberhardt, Markus (IMF Working Papers; Working Paper ;, 2018)
We develop an empirical model to predict banking crises in a sample of 60 low-income countries (LICs) over the 1981-2015 period. Given the recent emergence of financial sector stress associated with low commodity prices in several LICs, we assign price movements in primary commodities a key role in our model. Accounting for changes in commodity prices significantly increases the predictive power of the model. The commodity price effect is economically substantial and robust to the inclusion of a wide array of potential drivers of banking crises. We confirm that net capital inflows increase the likelihood of a crisis; however, in contrast to recent findings for advanced and emerging economies, credit growth and capital flow surges play no significant role in predicting banking crises in LICs.